Chest sonography versus chest radiograph in children admitted to paediatric intensive care – A prospective study. (July 2021) - Sachdev, Anil; Khatri, Anuj; Saxena, Kamal K; Gupta, Dhiren; Gupta, Neeraj; Menon, Geetha R
There is a paucity of studies on the correlation between chest radiograph and ultrasound (US) in children. Our objective was to study the correlation between bedside chest radiograph and ultrasound findings in 413 children with 1002 episodes of chest radiograph and US enrolled for a prospective, double-blinded observational study in a multidisciplinary paediatric intensive care unit. Weighted κ statistic for agreement was different for right and left lungs and varied from 50% for left pleural effusion to 98% for right pneumothorax. Pulmonary oedema, pneumothorax and pleural effusion were diagnosed by ultrasound alone in a significantly higher number of patients as compared to chest radiograph (P = 0.001). Chest ultrasound is therefore deemed more sensitive than chest radiograph in detection of pleural effusion, pulmonary oedema and pneumothorax.